Implementation of Google Classroom-Based Educational Technology Through Classroom Action Research to Improve Science Learning Activities of Eighth Grade Students at SMP Muhammadiyah Rappang - M, Usman; Hermansyah, Sam; Ridwan; Mutiara (Universitas Muhammadiyah Enrekang, 2026)
This study aimed to improve students’ science learning activities through the implementation of Google Classroom-based educational technology using a Classroom Action Research (CAR) approach. The research was conducted at SMP Muhammadiyah Rappang during the 2025/2026 academic year. The participants consisted of 58 eighth-grade students. The study employed two cycles of Classroom Action Research, including planning, action, observation, and reflection stages. Data were collected through classroom observations, student activity sheets, interviews, and documentation. The indicators of learning activities included students’ participation in discussions, assignment completion, responsiveness during online learning, collaboration, and engagement in science learning tasks. The collected data were analyzed using descriptive qualitative and quantitative methods. The findings revealed that the implementation of Google Classroom significantly improved students’ learning activities in science classes. In the first cycle, student participation and engagement were categorized as moderate, while in the second cycle, there was a considerable increase in active participation, collaboration, and learning responsibility. The average percentage of student learning activities increased from 64.3% in Cycle I to 85.7% in Cycle II. The use of Google Classroom also enhanced communication between teachers and students, facilitated access to learning materials, and encouraged independent learning. Therefore, the integration of Google Classroom-based educational technology through Classroom Action Research was effective in improving the science learning activities of eighth-grade students. The study suggests that digital learning platforms can serve as innovative instructional media to support interactive and student-centered learning environments in junior high schools.